The Man behind the Queen
XV, 264 p.
Keywords: From the 14th-century king consorts of Navarre to the modern European prince consorts of the 20th century, the male consort has been a peculiar yet recurrent historical figure. In this impressively broad collection, leading historians of monarchy analyze how male partners of female rulers have negotiated their unique roles throughout history.